Teachers' Motivation in Private Schools of Nepal (A study of Kathmandu Metropolitan City Ward Number-16) - K.C., Arjun (Rural Development Journal, 2017)
Motivation is the process that activates, guides, and maintains goal-directed behaviors. When it comes to motivating people to do their best in service of the organization it is fundamental. This paper explored the factors that are likely able to demonstrate the motivation expansion of teachers’ motivation. In relation to organizational performance, motivation is known to have an extensive history with a wide literature detailing discussions and studies. This study uses a combination of explorative and descriptive designs to explore teacher motivation in private schools. The data were collected through questionnaires and content analysis. The results indicate that motivational issues and other incentives have an effect on teacher motivation among private schools. When teachers are offered a competitive salary, a workplace that is pleasant, an element of autonomy, leading to basic recognition through bonuses, this is turning the work of teachers into a source of well-being. It is recommended that enlarging and updating these incentive packages for future satisfaction by teachers.